If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = w + -9 Reorder the terms: 6 = -9 + w Solving 6 = -9 + w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. 6 + -1w = -9 + w + -1w Combine like terms: w + -1w = 0 6 + -1w = -9 + 0 6 + -1w = -9 Add '-6' to each side of the equation. 6 + -6 + -1w = -9 + -6 Combine like terms: 6 + -6 = 0 0 + -1w = -9 + -6 -1w = -9 + -6 Combine like terms: -9 + -6 = -15 -1w = -15 Divide each side by '-1'. w = 15 Simplifying w = 15
| 7=-7n | | 14=v+14 | | 3x+5x+16= | | 5x+8x+12= | | 4x+56=7x-7 | | B*(ln(10*A))=2.995732274 | | B*LN(10a)=2.995732274 | | (3+-2)+6=2 | | .09x+.05(x-2000)=306 | | -2t(t-4)=10-2t | | 2x^2-2xy-y^2+8=0 | | a(b-x)-a(b-1)=a(ay-b) | | 2x^2-2xy-y^2-8=0 | | 25x-3=8x | | 10r+40=12r-6 | | n^2-25+10n=n^2+25 | | 6(3x-2)-5(6x-1)=3(x-8)-5(7x-6) | | 2[3-2(z+4)]=3(4+z) | | 3x+5y=184 | | -2.5x=38.00 | | (3t-8)(3t-8)=0 | | 2b(2a-x)=(b-a)+a(x+b) | | 6x=3x-15 | | 2x+6-6x=22 | | 4=2m+8 | | X^3+7x^2-9x-15=0 | | .07x+.05(x-1900)=253 | | X^3-19x^2-3x+17=0 | | 3(x+8)=2(x-9) | | 5-12y=0 | | 2(x+2)=3(2x+8) | | X=10.5 |